Separating invariants for arbitrary linear actions of the additive group - Dufresne, E; Elmer, J; Sezer, M (Springer Berlin Heidelberg, 2013)
We consider an arbitrary representation of the additive group GaGa over a field of characteristic zero and give an explicit description of a finite separating set in the corresponding ring of invariants.